Gestational Thrombocytopenic Patients in Our Center: Analysis of the Patients and Review of the Literature - Emel Ebru Özçimen (Medical Network, 2016)
OBJECTIVE: Gestational thrombocytopenia is the most common cause of the thrombocytopenia in pregnancy. The aim of this study was to determine the prevalence of gestational thrombocytopenia (GT) among pregnant women in our center. STUDY DESIGN: Platelet count was analyzed in 452 pregnant women. The patients were divided according to severity of thrombocytopenia. RESULTS: Forty-five patients were thrombocytopenic. Six patients were severe, 16 patients were moderate and 23 patients were mild thrombocytopenic. The prevalence of GT was found 9.9 %. CONCLUSION: Gestational thrombocytopenia is usually observed as mild form.